Teaching Ferguson: Can #BlackLivesMatter in the Neoliberal University?. Issue 2 (2nd April 2016) - Dowling, Sarah; Johnson, Marcus; Krabill, Ron
Abstract : In the wake of protests following the nonindictments of police for the killing of unarmed African Americans in Ferguson and elsewhere, schools across North America created courses discussing historical and contemporary events leading up to these deaths and the #BlackLivesMatter movement. The authors created and taught such a course during the winter of 2015; this article reflects on our experience and places it within the context of neoliberal higher education in the United States to further examine the opportunities presented and the obstacles encountered for thinking through questions of race, class, and inequality in these timely—some might say reactionary—course offerings. Neither panacea nor abject failure, we understand these courses as embedded in ongoing struggles taking place within the university, just one of the many institutions in which antiracism efforts are continually occurring—with varying degrees of success.